Monitoring English Word Pronunciation Cognition Knowledge of Bilingual School Teachers in Central Java - Satiti, Laras Hayu (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
The purpose of this study is to determine the knowledge level of cognition in English word pronunciation held by homeroom teachers working in one of Central Java bilingual schools. It is required that teachers provide their students with an authentic model of proper pronunciation while working with Cambridge International Primary Program (CIPP) related subjects. It is possible to demonstrate whether or not teachers engage in metacognition consciousness with regard to pronunciation of English words by monitoring students' knowledge of cognitive in English word pronunciation. It is crucial to have this information in order to pick future tactics to improve their pronunciation abilities through the provided training. It is easier for the teachers to avoid misleading their pupils with the material that they present while they are teaching. In order to collect the necessary data and carry out the recorded pronunciation test, a questionnaire with closed-ended questions was administered first. After that, a matrix was utilized to monitor the subject's metacognition consciousness in relation to the pronunciation test being conducted. According to the findings, their level of metacognitive awareness ranges from low to moderate levels.